Angiotensin Converting Enzyme 2 (ACE2) G8790A Gene Polymorphism as a Risk Factor for Essential Hypertension - Husna, Nazaul; Nauphar, Donny; Pratamawati, Tiar Masykuroh (Yayasan Aliansi Cendekiawan Indonesia Thailand (Indonesian Scholars' Alliance), 2025)
Background: Globally, the number of people with hypertension has doubled, from 650 million to 1.3 billion. The World Health Organization reported that hypertension is responsible for more than 10 million deaths every year. Essential hypertension is a multifactorial condition with genetics as one of the factors. Genome-Wide Association Study has identified several genes associated with hypertension, one of which is the Angiotensin Converting Enzyme 2 (ACE2) gene. Essential hypertension may be predisposed to by the G8790A polymorphism of the ACE2 gene, which is hypothesized to interfere with the normal function of the Renin Angiotensin System (RAS). Aims: The purpose of this study is to determine whether the ACE2 G8790A gene polymorphism in Cirebon, West Java, Indonesia, is associated with an increased risk of essential hypertension. Methods: This is a case-control study conducted at the Talun Health Center, Cirebon Regency, April-August 2024, involving 30 essential hypertensive patients and 30 healthy controls. The study population comprised adults aged 30 to 72 years. Data was obtained through the examination of blood pressure, DNA extraction, PCR-RFLP with ALUI restriction enzyme, and then visualization of the results with Gel Electrophoresis. The Chi-Square Test technique and the Odds Ratio (OR) computation were used to analyze the data. Results: The G allele was higher in the case group 33 (55%), while the A allele was higher in the control group 34 (56.7%). The statistical analysis showed that there was no significant link between the ACE2 G8790A gene variation and essential hypertension, with a p-value of 0.592 (p > 0.05) (OR = 0.750; CI = 0.262–2.151). Conclusion: The ACE2 gene G8790A polymorphism and the rate of hypertension in Cirebon, West Java, were not significantly correlated. Further research is required on a larger scale to investigate the effects of gene combinations or interactions with other locus genes on essential hypertension.